Kebisingan dan Stres Kerja Karyawan PT PLN (Persero) Kairatu - Eka Safitri Sillehu; Indriati Paskarini; Fatima Tatroman; Sahrir Sillehu (FORIKES, 2022)
Noise is a physical hazard factor that is often found in the work environment. The detrimental impact that is often felt by workers is work stress. So research is needed which aims to determine the effect of noise on work stress in employees of PT PLN (Persero) Kairatu Diesel Electricity Center Service Unit. The research design was cross-sectional. The research subjects were 28 employees who worked at the Kairatu Diesel Electric Central Service Unit who were selected by total sampling technique. Primary data were obtained from questionnaires and sound level meters and secondary data were obtained from the archives of PT PLN (Persero) Kairatu. The data obtained were analyzed using the Chi-Square test. The results of the analysis show that the value of p = 0.02 means that there is a relationship between noise and work stress.Keywords: noise; work stress; diesel power center ABSTRAK Kebisingan merupakan salah satu faktor bahaya fisik yang sering dijumpai di lingkungan kerja. Dampak merugikan yang sering dirasakan oleh para pekerja yaitu stres kerja. Maka diperlukan penelitian yang bertujuan untuk mengetahui pengaruh kebisingan terhadap stres kerja pada karyawan PT PLN (Persero) Unit Layanan Pusat Listrik Diesel Kairatu. Desain penelitian ini adalah cross-sectional. Subyek penelitian adalah 28 karyawan yang bekerja di Unit Layanan Pusat Listrik Diesel Kairatu yang dipilih dengan teknik total sampling. Data primer diperoleh dari kuesioner dan alat sound level meter dan sekunder diperoleh dari arsip PT PLN (Persero) Kairatu. Data yang diperoleh dianalisis menggunakan uji Chi-Square. Hasil analisis menunjukkan nilai p = 0,02 yang berarti ada hubungan antara kebisingan dengan stress kerja.Kata kunci: kebisingan; stress kerja; pusat listrik tenaga diesel